3D Printing of Electrochemical Energy Storage Devices: A Review of Printing Techniques and Electrode/Electrolyte Architectures. Issue 2 (9th January 2020) - Cheng, Meng; Deivanayagam, Ramasubramonian; Shahbazian‐Yassar, Reza
Abstract: Recently, the fabrication of electrochemical energy storage (EES) devices via three‐dimensional (3D) printing has drawn considerable interest due to the enhanced electrochemical performances that arise from well‐designed EES device architectures as compared to the conventionally fabricated ones. This work summarizes the developments in electrochemical devices fabricated by 3D printing techniques. We have categorized this review based on the architectural design of 3D printed EES devices: interdigitated structures, 3D scaffolds, and fibers. The printing techniques, processes, printing materials, advantages, and disadvantages of 3D printed architectures are systematically discussed in this review. Enhanced power density and energy density values were obtained using interdigitated structures and 3D scaffolds, in comparison with the conventional planar structure. The reasons for better electrochemical performances can be attributed to the presence of higher loading active materials, larger footprint area, and shorter ion transport route. The 3D printing techniques have also enabled the EES devices to be fabricated into lightweight, flexible fibers, and to be integrated into wearable electronics. At the end, the challenges and outlooks on the fabrication of 3D structured EES devices are outlined. Abstract : Architectural aesthetics : In this review, the architectural designs of 3D printed electrochemical energy storage (EES) devices are categorized into interdigitated structures, 3D scaffolds, and fibers. The 3D printing techniques, processes, printing materials, and performances of 3D printed EES devices architectures are systematically discussed. Furthermore, the challenges and outlooks on the fabrication of 3D structured EES devices are also provided.